2016
DOI: 10.1088/0957-4484/27/45/455601
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy of InAs nanowires in SiO2nanotube templates: challenges and prospects for integration of III–Vs on Si

Abstract: Guided growth of semiconductor nanowires in nanotube templates has been considered as a potential platform for reproducible integration of III-Vs on silicon or other mismatched substrates. Herein, we report on the challenges and prospects of molecular beam epitaxy of InAs nanowires in SiO 2 /Si nanotube templates. We show how and under which conditions the nanowire growth is initiated by In-assisted vapor-liquid-solid growth enabled by the local conditions inside the nanotube template. The conditions for high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…The nano-bridges are particularly interesting since the second 'leg', which is formed after the second annealing step, grows in 〈111〉A direction. A-polar growth is very untypical for selfcatalyzed arsenide nanowires, and has only recently been observed in the case of InAs growing around Si/SiO 2 nanotubes [47]. Our results confirm that it is possible under certain conditions.…”
Section: Resultssupporting
confidence: 72%
“…The nano-bridges are particularly interesting since the second 'leg', which is formed after the second annealing step, grows in 〈111〉A direction. A-polar growth is very untypical for selfcatalyzed arsenide nanowires, and has only recently been observed in the case of InAs growing around Si/SiO 2 nanotubes [47]. Our results confirm that it is possible under certain conditions.…”
Section: Resultssupporting
confidence: 72%
“…To gain access to this stage, we characterized the seeds below the gallium droplets, formed in the initial stage of growth after the gallium pre-deposition. We have recently shown that the incubation time required to start the nanowires can be as long as a few minutes 22 . We have also found that the distribution of the incubation times can be quite broad for low degrees of supersaturation in the vapor phase 22 .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the incubation time required to start the nanowires can be as long as a few minutes 22 . We have also found that the distribution of the incubation times can be quite broad for low degrees of supersaturation in the vapor phase 22 . This broad distribution gives a more representative picture of possible initial configurations of the nanowire growth seeds.…”
Section: Resultsmentioning
confidence: 99%
“…To give an example, silicon nanowires could be first etched on a substrate. These could be used as templates to initiate growth of III-V nanowires on their tips and create an axial heterostructure [52,275,276]. Likewise, etched III-V nanowire structures could benefit from passivation with a subsequent radial growth of a higher bandgap material.…”
Section: Nanowire Heterostructure Formation: Growth Vs Etchingmentioning
confidence: 99%